Pelatihan F&B Service dalam Meningkatkan Kualitas Pelayanan terhadap Konsumen di Desa Wisata Bongan - Ni Nyoman Widani; Billy Tanius; I Gusti Ayu Ari Agustin (LPPM Universitas Bumigora, 2022)
Industrial Revolution 4.0 is a term that is already familiar to people in Indonesia. The development of technology and information occurs so quickly that it has a huge impact on the industrial world as well as human behavior. This behavior affects how the tourism industry players provide services to consumers who come to visit the tourist village of Bongan Tabanan - Bali. Bongan Village as a tourist village also has culinary products that use the main ingredients of the Gonda plant. Gonda plant itself is known as one of the commodities that have economic value apart from rice plants. Ease in the cultivation process and lower operational value are an advantage for farmers compared to planting rice. Processed products from the gonda plant are offered directly when tourists come to visit the tourist village of Bongan. To achieve tourist satisfaction and increase purchases of Gonda processed products, culinary actors must be able to provide services or services that are managed professionally so as to provide satisfaction to customers or foreign tourists who visit. During the Covid-19 pandemic, technological advances began to be used as F&B services, one of which was using online media, such as Facebook, Instagram, Twitter and other websites. The purpose of Community Service Activities in Bongan Village is expected through F&B Service Training to improve the quality of service to consumers in the tourist village of Bongan, Tabanan.